Where did she come from, and where did she go to? (the Queen of Heaven in Jeremiah 7 and 44) - De Villiers, Gerda (Old Testament essays, 2002)
The identity of the Queen of Heaven is obscure and will probably never be revealed. Instead of joining this debate my brief article takes as point of departure the discourse between Jeremiah and the Judahites in Jeremiah 44 : 15-24. Both parties reinvent the same history, but do so from opposing points of view. Therefore the article focuses on the Queen of Heaven as a discoursive subject and proposes that religious discourse constructed as well as effaced her. I conclude that discourse is a powerful means which determines reality : recent theological discourse should be aware of its constructive power but realise that exactly within this power lies the danger of its own deconstruction.